PENERAPAN PERENCANAAN PAJAK ATAS PAJAK PENGHASILAN PASAL 21 SEBAGAI STRATEGI PENGHEMATAN PEMBAYARAN PAJAK PERUSAHAAN - Dhefina Fiorensya Meidy, Fadjar Harimurti & Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2017)
The purpose of this study to compare the effect of applying the calculationmethod selection section 21 of Income Tax on income received by employees as astrategy in tax savings and tax planning implementation of Article 21 Income Tax onthe income of employees as in the tax-saving strategies. This research was conductedin PDAM Surakarta. The study population was the employees of PDAM Surakartamany as 349 employees remained. A sample of 72 people with technique StratifiedSample. Data were analyzed used quantitative descriptive analysis. The resultsshowed that the use of gross-up method can provide benefits to employees of PDAMSurakarta because employees no longer pay income tax and Surakarta PDAM canhelp companies to minimize income taxes to be paid. Effect of income tax planningsection 21 of the Income Tax Article 25, namely the existence of tax planning canincrease the amount of income tax payable article 21 PDAM Surakarta, but thesecosts can be expensed in the income tax article 25 for being extra income foremployees.Keywords: tax planning, income taxes, tax savings